Association of Anthropometric and CT-Based Obesity Indices with Subclinical Atherosclerosis - Torii, Sayuki; Watanabe, Yoshiyuki; Kondo, Keiko; Hisamatsu, Takashi; Sawayama, Yuichi; Fujiyoshi, Akira; Kadowaki, Sayaka; Ueshima, Hirotsugu; Yano, Yuichiro; Nakagawa, Yoshihisa; Miura, Katsuyuki; Higo, Yosuke; et al. (Journal of Atherosclerosis and Thrombosis, 2024)
Aim: Few studies have compared the strength in the associations of anthropometric and computed tomography (CT)-based obesity indices with coronary artery calcification (CAC), aortic artery calcification (AoAC), and aortic valve calcification (AVC).Methods: We assessed cross-sectcional associations of anthropometric and CT-based obesity indices with CAC, AoAC, and AVC. Anthropometric measures included body mass index (BMI), waist circumference, hip ircumference, waist-to-hip circumference ratio, and waist-to-height ratio in 931 men (mean age, 63.7 years) from a population-based cohort. CT images at the L4/5 level were obtained to calculate the areas of abdominal visceral adipose tissue (VAT), subcutaneous adipose tissue (SAT), total adipose tissue (TAT), VAT-to-SAT ratio (VSR), and VAT-to-TAT ratio (VTR). CAC, AoAC, and AVC were quantified using the Agatston score based on CT scanning. Results: CAC, AVC, and AoAC were present in 348 (62.6%), 173 (18.6%), and 769 (82.6%) participants, respectively. In multivariable models adjusting for age, lifestyle factors, and CT types (electron beam CT and multidetector row CT), anthropometric and CT-based obesity indices were positively associated with CAC (p＜0.01). Conversely, VAT-to-SAT ratio and VAT-to-TAT ratio were positively associated with AoAC (p＜0.01). Any obesity indices were not associated with AVC.Conclusions: The strength of the associations of obesity indices with subclinical atherosclerosis varied according to the anatomically distinct atherosclerotic lesions, among men.